2015
DOI: 10.2174/1874110x01509012755
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regression Model Based on Weather Factors for Predicting The Heat Load of A District Heating System in Dalian, China—A Case Study

Abstract: The managers need to have a reasonable guide on the operation and management in district heating system (DHS), so it's very necessary to predicting the heat load for DHS. In this paper, the relationships between the heat load and weather conditions have been researched in order to determine the inputs variables and output variable of the future heat load prediction model. Using the given data from the obtained database, the multiple regression modelling and analysis method was carried out so as to establish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…"Multiple linear regression (MLR) is the standard and simplest approach for the development of calibration models. Feature selection in the form of stepwise MLR (SMLR) gives good results over large datasets [7,8,9]. A stepwise regression procedure was adopted for the selection of the best regression variable among many independent variables and found that models were able to explain 51 to 79% variability for rice yield.…”
Section: Introductionmentioning
confidence: 99%
“…"Multiple linear regression (MLR) is the standard and simplest approach for the development of calibration models. Feature selection in the form of stepwise MLR (SMLR) gives good results over large datasets [7,8,9]. A stepwise regression procedure was adopted for the selection of the best regression variable among many independent variables and found that models were able to explain 51 to 79% variability for rice yield.…”
Section: Introductionmentioning
confidence: 99%
“…At a high temporal resolution (e.g., 3 h), the reanalysis data are still at a coarse spatial resolution [e.g., 0.25 • (latitude) × 0.3125 • (longitude)], and thus cannot provide local variations at a fine spatial scale for wind speed, which is affected by prevailing pressure, air temperature and local site characteristics with a volatile nature. Additionally, such finely resolved variability of wind speed also might not be captured well (low accuracy) by traditional approaches, including multiple linear regression [12], nonlinear regression [13] and spatial interpolation [14,15] (e.g., inverse distance weighting or kriging) due to the sparse spatial distribution of wind speed monitoring stations, and the limited generalization of these methods compared to advanced machine learning methods, such as XGBoost and deep learning.…”
Section: Introductionmentioning
confidence: 99%